2004
DOI: 10.1084/jem.20040973
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cell Ontogeny Defined by Quantitative Changes in Blimp-1 Expression

Abstract: Plasma cells comprise a population of terminally differentiated B cells that are dependent on the transcriptional regulator B lymphocyte–induced maturation protein 1 (Blimp-1) for their development. We have introduced a gfp reporter into the Blimp-1 locus and shown that heterozygous mice express the green fluorescent protein in all antibody-secreting cells (ASCs) in vivo and in vitro. In vitro, these cells display considerable heterogeneity in surface phenotype, immunoglobulin secretion rate, and Blimp-1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
561
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(605 citation statements)
references
References 44 publications
37
561
1
3
Order By: Relevance
“…1B). Their GFP fluorescence intensity increased with time (not shown), as expected given the increase of Blimp-1 expression in terminally differentiated PCs (1). Altogether, these observations validated the FIGURE 1.…”
Section: Distribution and Preferential Proximity Of Pcs In The Bm Comsupporting
confidence: 84%
See 1 more Smart Citation
“…1B). Their GFP fluorescence intensity increased with time (not shown), as expected given the increase of Blimp-1 expression in terminally differentiated PCs (1). Altogether, these observations validated the FIGURE 1.…”
Section: Distribution and Preferential Proximity Of Pcs In The Bm Comsupporting
confidence: 84%
“…PCs may persist for decades throughout the body, namely at sites of inflammation, but predominantly in the bone marrow (BM) compartment. A complex orchestration guides Ag-specific B cells to exit the germinal centers of lymphoid organs and migrate toward the BM, a privileged location where they receive additional signals required for their final differentiation and prolonged survival (1). There is strong evidence that the longevity of BMPCs is dependent on environmental factors (2) (i.e., their access to specific survival niches).…”
mentioning
confidence: 99%
“…2B, right panel) and miR-148a expression, one could argue that miR-148a controls plasmablast differentiation. In this case, B cells that have upregulated miR-148a expression should be determined for the PC differentiation pathway and, in line with this, should have induced the expression of Blimp-1, a PC signature transcription factor.To address this point, we isolated naive B cells from the spleens of mice carrying a GFP reporter knock-in under control of the Blimp-1 promoter [19] and monitored the changes in the frequency of Blimp-1:GFP-positive cells and miR-148a abundance in cultures before and 72 h after the addition of various B-cell stimuli (LPS, LPS+anti-IgM, CpG, anti-CD40+anti-IgM+IL-4 or anti-CD40+IL21). TaqMan qRT-PCR and GFP fluorescence analyses clearly revealed that the extent of miR-148a upregulation (Fig.…”
mentioning
confidence: 99%
“…Apart from being stable over an indeWnite number of cell divisions, this approach also oVers several other advantages: (1) combinatorial expression of mixtures of diVerent XFP allows the staining of individual cells in all colors of the visible spectrum within the same animal (Livet et al 2007), (2) expression driven by deWned promoters enables cell type-speciWc labeling, such as the network of dendritic cells in peripheral lymphatic tissues (Lindquist et al 2004) or microglia in the brain (Jung et al 2000), (3) the same approach can also lead to development-speciWc expression of XFP, such as in BLIMP1-GFP mice, that harbor green plasma cells of the B lineage (Kallies et al 2004) and Wnally (4) the fusion of XFP with organelle-speciWc proteins or localization signals can lead to stable Xuorescent staining of the target structures, such as mitochondria (Misgeld et al 2007) or the DNA in the nucleus (Hadjantonakis and Papaioannou 2004). (5) Another useful approach, based on XFP is the generation of genetically encoded sensors that, e.g., allow cell-type-speciWc calcium imaging in vivo without the need of dye application (Wallace et al 2008).…”
Section: Visualization Of Leukocytes and Organ Structurementioning
confidence: 99%
“…For example, Lindquist et al (2004) have shown that, using transgenic mice with dendritic cell (DC)-speciWc expression of enhanced YFP, DCs are enmeshed in an extensive network and remain in place within peripheral lymph nodes in vivo. Kallies et al (2004) used transgenic mice, where GFP was targeted to the Blimp1 locus, to analyze the kinetics and cellular subtypes of plasma cell diVerentiation (Kallies et al 2004). However, it is not always advisable to use XFP-transgenic mice directly or choose a model where all cells of a given lineage express the XFP-protein for imaging.…”
Section: Visualization Of Leukocytes and Organ Structurementioning
confidence: 99%